Analysis of Determination Toward Return On Assets of Islamic Commercial Banks - Laura Wulandari; Muhammad Hafizh; Mukhlish M.Nur (eCo-Fin, 2025)
This study investigates the influence of Fee-Based Income (FBI), Green Finance (GF), Third Party Funds (TPF), and Corporate Governance (GCG) on the Return on Assets (ROA) of Islamic Commercial Banks (ICB) in Indonesia during the 2019–2023 period. Recognizing the importance of assessing a bank's financial health to guide strategic improvements, the study adopts a quantitative method with a descriptive approach. Data were obtained through purposive sampling from a population of 13 Islamic Commercial Bank (ICB), resulting in a sample of 10 ICB, with a total of 50 observations (10 banks × 5 years). The data analysis was conducted using panel data regression with the Common Effect Model in EViews 12. The findings reveal that, simultaneously, FBI, GF, TPF, and GCG have a significant positive effect on ROA. However, partially, only TPF and GCG show a significant impact (p < 0.001), while FBI and GF do not significantly influence ROA. The model's explanatory power is indicated by an R² value of 0.438, suggesting that 43.8% of the variation in ROA can be explained by the four independent variables. These results emphasize the strategic importance for Islamic banks to focus on enhancing third-party funds and corporate governance to improve financial performance. if you'd like this adapted into an abstract, research summary, or journal-style format. ears, the model uses the Common Effect Model with an R² of 0.484.